New Evaluations and Restitution Suggestions for the Small Bath Structure at Phaselis - Çiğdem ÖNER (Phaselis: Disiplinlerarası Akdeniz Araştırmaları Dergisi)
Phaselis, located within the administrative boundaries of the Kemer District of Antalya Province, was founded on a promontory extending towards the sea on the eastern coast of the Teke Peninsula. The Phaselis Small Bath is one of the public buildings located on the main street between the north-south harbours in the city plan. The objective of this article is to analyse and interpret in conjunction with other examples from Eastern Mediterranean port cities the building, which was first identified as a bath by the director of Antalya Museum (head of the excavation) Kayhan Dörtlük in 1980. The initial studies conducted under the direction of Cevdet Bayburtluoğlu between 1981 and 1985 were subjected to analysis, and the architectural design of the building was re-documented utilising contemporary technologies. The position, typology and construction technique of the bath structure in Phaselis settlement archaeology was examined, and restitution proposals have been prepared with the intention of supporting the interpretation of the period characteristics of the bath structures by making use of digital archaeology.